2008
DOI: 10.1128/mcb.01697-07
|View full text |Cite
|
Sign up to set email alerts
|

Centrin 2 Localizes to the Vertebrate Nuclear Pore and Plays a Role in mRNA and Protein Export

Abstract: Centrins in vertebrates have traditionally been associated with microtubule-nucleating centers such as the centrosome. Unexpectedly, we found centrin 2 to associate biochemically with nucleoporins, including the Xenopus laevis Nup107-160 complex, a critical subunit of the vertebrate nuclear pore in interphase and of the kinetochores and spindle poles in mitosis. Immunofluorescence of Xenopus cells and in vitro reconstituted nuclei indeed revealed centrin 2 localized at the nuclear pores. Use of the mild deterg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 143 publications
(181 reference statements)
2
68
0
1
Order By: Relevance
“…In addition, our IF experiments in parental HeLa cells using antibodies specific for different TREX-2 subunits showed that GANP is localized predominantly at the nuclear envelope while PCID2 is found at the nuclear periphery along with a cytoplasmic and nuclear staining. Finally, both CETN2 and CETN3 localized at the centriole as reported earlier (Middendorp et al, 1997;Trojan et al, 2008;Resendes et al, 2008) and also displayed a perinuclear staining ( Fig. 1D; supplementary material Fig.…”
Section: Trex-2 Is Localized At the Nuclear Periphery Independently Osupporting
confidence: 53%
“…In addition, our IF experiments in parental HeLa cells using antibodies specific for different TREX-2 subunits showed that GANP is localized predominantly at the nuclear envelope while PCID2 is found at the nuclear periphery along with a cytoplasmic and nuclear staining. Finally, both CETN2 and CETN3 localized at the centriole as reported earlier (Middendorp et al, 1997;Trojan et al, 2008;Resendes et al, 2008) and also displayed a perinuclear staining ( Fig. 1D; supplementary material Fig.…”
Section: Trex-2 Is Localized At the Nuclear Periphery Independently Osupporting
confidence: 53%
“…Although little is presently known about a possible role of SUMO at the centrosome, recent studies have identified several proteins that undergo SUMOylation and are known to localize to both centrosomal structures and the nuclear compartment (Cheng et al, 2006;Haindl et al, 2008;Yun et al, 2008). Our present data suggest that the SUMOylation machinery does not influence centrin-2 localization to the centrosome but is required for the efficient accumulation of the protein in the nucleus, where it functions in NER and mRNA export (Fischer et al, 2004;Resendes et al, 2008). A priori, the nuclear accumulation of centrin-2 could be regulated at the level of transport or retention (or both).…”
Section: Discussionmentioning
confidence: 45%
“…Remarkably, ~90% of the centrin-2 protein is not associated with centrosomal structures (Paoletti et al, 1996) and instead much of it is present within the nucleus. In line with this localization, centrin-2 has been implicated in mRNA export from the nucleus (Resendes et al, 2008) and this function seems to be conserved (Fischer et al, 2004). Furthermore, within the nucleus, centrin-2 associates with the xeroderma pigmentosum group C (XPC) protein and the human homolog of Rad23 B (HR23B) to form the trimeric XPC complex (Araki et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Centrins are small calcium binding proteins that function at centrioles and basal bodies but also in a diverse array of additional activities including nuclear export and DNA damage repair (Chen and Madura, 2008;Fischer et al, 2004;Nishi et al, 2005;Paoletti et al, 1996;Resendes et al, 2008;Yang et al, 2010). Presumably, specificity of localization and function is accomplished through centrin-binding partners.…”
Section: Introductionmentioning
confidence: 99%